2012
DOI: 10.1186/gb-2012-13-4-r31
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of transcriptome differences between the founder strains of the rat HXB/BXH recombinant inbred panel

Abstract: BackgroundWith the advent of next generation sequencing it has become possible to detect genomic variation on a large scale. However, predicting which genomic variants are damaging to gene function remains a challenge, as knowledge of the effects of genomic variation on gene expression is still limited. Recombinant inbred panels are powerful tools to study the cis and trans effects of genetic variation on molecular phenotypes such as gene expression.ResultsWe generated a comprehensive inventory of genomic diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…Therefore we excluded approximately 0.9 M positions per strain where 25-75% of the reads supported the variant allele. Almost 10% of these variants are detected in regions with high coverage (>30X), compared to <1% for homozygous SNVs, and may be due to duplications, as suggested previously [40]. Further, we found that 7% of the heterozygous SNVs in DA/O (coverage 9-25X) were called as homozygous SNVs in DA/K, whereas 1% were called as reference.…”
Section: Methodssupporting
confidence: 84%
“…Therefore we excluded approximately 0.9 M positions per strain where 25-75% of the reads supported the variant allele. Almost 10% of these variants are detected in regions with high coverage (>30X), compared to <1% for homozygous SNVs, and may be due to duplications, as suggested previously [40]. Further, we found that 7% of the heterozygous SNVs in DA/O (coverage 9-25X) were called as homozygous SNVs in DA/K, whereas 1% were called as reference.…”
Section: Methodssupporting
confidence: 84%
“…The resulting libraries were sequenced on an Illumina HiSeq2000 following the manufacturer’s instructions. We also sequenced the genome of BN/Mcwi, the rat strain from which the reference BN rat genome was derived, on the SOLiD sequencing platform, using protocols previously described (Simonis et al., 2012), to identify and exclude potential sequencing errors in the reference genome.…”
Section: Methodsmentioning
confidence: 99%
“…Previous genomic and physiological studies generated large lists of candidate genes [86][87][88]. The inherited hypertension phenotype in this model suggests that disease is caused by a genetic defect that should manifest itself at the transcriptome and proteome levels.…”
Section: Proteogenomics Data Integration -An Examplementioning
confidence: 96%